(untitled) (Latin-American Journal of Computing, 2020)
Software-defined Networking (SDN) constitutes a new era in the development of internetworking. The SDN paradigm splits the data plane from the control plane. It uses controller equipment, which is responsible for centrally managing several network devices simultaneously. This study analyzes three open-source controllers for SDN based on the OpenFlow protocol. Specifically, the performance of FloodLight, OpenDayLight (ODL), and Ryu controllers is evaluated in terms of latency, throughput, and scalability. In doing so, the Cbench tool is used in an emulated environment with Mininet. The results show that the Ryu controller presents the lowest performance in all the evaluated parameters; ODL provides lower latency and FloodLight higher throughput. Regarding scalability, we conclude that Floodlight can be used in small networks, whereas ODL can be used in dense networks. Furthermore, we evaluate their main characteristics, which must be considered for their choice prior to implementation and deployment.